Complications in the Treatment of Mandibular Condylar Fracture, Surgical Versus Non-Surgical Treatment - Tehreem Khan, Maria Shabbir (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The facial fractures include Condylar fractures are most common in mandibular fractures, which have the highest fracture incidence after nasal bone fractures. Three different traumatic forces can result in condylar injury: the first is energy imparted to a static person by a moving object, such as a blow to the face from a cricket bat; the second is a moving person striking a static object, such as a child falling and striking the ground; and the third is a combination of the first two forces, such as when a person is moving and an automobile is moving and is hit by an automobile. This kind of force typically has the biggest impact and causes the most severe injury patterns. Objective: To compare frequency of Complications of two procedures for the treatment of mandibular condylar fracture surgical versus conservative treatment. Methodology: This Randomized control trial was held in the Tertiary Care Hospital Karachi for 6 months from 12 Jul, 2019 to 12 Jan, 2020. ERC were taken before data collection. Patients suffering from mandibular condylar fracture and fulfilling exclusion and inclusion criteria and who were ready to give informed consent after explaining study protocol, risk benefit ratio and data usage for research were included in our study. The first group labelled as "A" was treated by closed reduction and immobilization and second group labelled as group "B" was undergone internal fixation and open reduction. Results: The mean age and standard deviation of the 72 patients was determined to be 40.85 ± 12.93 years, respectively, with the 18 years was the minimum age and the 65 years being maximum. Frequency of gender was shown in Graph 1.The minimum duration of fracture was 1 day, and maximum were 7 days. The minimum mouth opening was 15mm and maximum was 35mm (Table 1). Trismus was present in 5/72 (6.9%) patients while it was absent in 67/72 (93.1%) patients (Table 2). Malocclusion was present in 20/72 (27.8%) patients while it was absent in 52/72 (72.2%) patients. Unilateral Side of fracture was present in 40/72 (55.6%) patients while Bilateral was present in 32/72 (44.4%) patients (Table 3) Conclusions: In conclusion, closed reduction had clinically satisfactory results, although open reduction and internal fixation produced more accurate to reduce the complications. Keywords: Closed reduction, Internal fixation, Open reduction,complications